Complex spinal fixation of a cervical vertebra Brown tumour: report of an unusual case. (2nd November 2019) - Toescu, Sebastian Miguel; Ibrahim, Maria; O'Donovan, Dominic G.; Balasubramaniam, Gowrie; David, Karoly M.
Abstract: Brown tumours affecting the cervical spine are a rare but recognised complication of renal failure-related secondary hyperparathyroidism. We present a case of a 26 year-old female with radiculopathy who was managed successfully with 360° cervical spine fixation and parathyroidectomy.